Community-Based Total Sanitation Practices in Families Suffering from Stunting in Raknamo Village, District Amabi Oefeto, Kupang Regency - Albina Bare Telan; Lidia Br Tarigan; Enni Rosida Sinaga; Yulia (Postgraduate, University of Mataram, 2025)
The stunting rate in Raknamo village is the highest with a total of 45 cases. The research objectives are: Analyzing the relationship between community-based total sanitation (STBM) practices and the incidence of stunting and analyzing the STBM practice factors that are most dominant in their relationship to the incidence of stunting. Therefore, research on STBM practices is very important to find out STBM factors that are related to stunting so that efforts can be made to prevent and overcome stunting. Types of qualitative and quantitative descriptive research (mixed methods). This approach was chosen to understand complex phenomena related to community-based total sanitation (STBM) practices in families of stunting sufferers, identify factors that influence the implementation of STBM, analyze the level of knowledge and community sanitation practices in depth. Qualitative research reveals subjective aspects, people's perceptions of STBM, quantitative research provides an accurate numerical picture of existing conditions. The results show that the defecation habits of respondents in cases with a latrine are 27 (69%), and families who do not have a latrine but still share are 12 (31%). (69%) have a private latrine, but there are still 31% who do not have a latrine and use shared facilities or defecate in the garden. The CTPS practice of families of toddlers with stunting is still low, only 33% always do it, while 64% sometimes do it. All families of toddlers with stunting (100%) boil water before consuming it, but only 79% keep the water source clean.